UM MÉTODO PARA SELEÇÃO DE SOFTWARE NA ENGENHARIA DE REQUISITOS - CANTANHÊDE FILHO, Paulino Almeida (2005)
Guidelines for evaluation and selection of COTS (Commercial-Off-The-Shelf) products. Comes a methodology for the Development based on COTS (DBC) in the Requirements Engineering, being approached the evaluation phases and selection of DBC. The method is divided in three phases, that are divided in activities orienting by actions that seek to the quality of the information for a socket of decision in an automated and oriented way for defined evaluation criteria during the Requirements Engineering. This approach divide the requirements in three levels: Fundamental, Contractual and Desirable. The functional and no-functional requirements are treated in an equalitarian way.